Turn Away the World: How a Curious Fifteenth-Century Spiritual Guidebook Shaped the Contours of the Reformation and Taught Readers to Turn Inward - Magill, R. Jay (Christianity & literature, 2017)
This paper contains a compact narrative history of the life of theologian Thomas à Kempis (1380-1471) and his curious spiritual guidebook The Imitation of Christ. It then continues with a brief analysis of how The Imitation shaped the contours of the Reformation, harkened back to the early Christian tradition of contemptus mundi, and eventually helped form modern ideas of intimacy and inwardness in the West.